2010
DOI: 10.1103/physrevb.82.054418
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of small Pt-capped Fe, Co, and Ni clusters: A density functional theory study

Abstract: Theoretical studies on M 13 (M = Fe, Co, Ni) and M 13 Pt n (for n = 3, 4, 5, 20) clusters including the spin-orbit coupling are done using density functional theory. The magnetic anisotropy energy (MAE) along with the spin and orbital moments are calculated for M 13 icosahedral clusters. The angle-dependent energy differences are modelled using an extended classical Heisenberg model with local anisotropies. From our studies, the MAE for Jahn-Teller distorted Fe 13 , Mackay distorted Fe 13 and nearly undistorte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 76 publications
5
51
1
Order By: Relevance
“…We will see that most of all the studied NPs have the same easy axis orientation as their bulk alloys. Also, the values of the total MAE obtained in this work are of order of tens of meV following the same trend shown by other groups for small NPs [31,32]. In the graphs, the MAE is expressed in meV per atom by dividing by the total number of atoms (magnetic plus non-magnetic) of each NP and using straight coloured lines we show the MAE values for each L1 0 alloy.…”
Section: Magnetic Anisotropysupporting
confidence: 86%
See 2 more Smart Citations
“…We will see that most of all the studied NPs have the same easy axis orientation as their bulk alloys. Also, the values of the total MAE obtained in this work are of order of tens of meV following the same trend shown by other groups for small NPs [31,32]. In the graphs, the MAE is expressed in meV per atom by dividing by the total number of atoms (magnetic plus non-magnetic) of each NP and using straight coloured lines we show the MAE values for each L1 0 alloy.…”
Section: Magnetic Anisotropysupporting
confidence: 86%
“…These clusters or nanoparticles (NPs) have properties different from those of bulk alloys due to their reduced surface atomic coordination. In particular, binary 3d-5d NPs formed by transition metals (TM) such as Fe or Co together with 5d noble metals like Au or Pt allow the possibility to tune the magnetic properties based on an in-depth knowledge of their geometrical [27][28][29] and magnetic behavior [30][31][32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10], it is shown that the calculated spin moment in general is in reasonable agreement with experiment. Although the calculated spin and orbital magnetic moments of Co 13 clusters capped with Pt [22] are available, there are no experimental data to compare with these calculations. The latter are also performed within GGA, which is in the present work shown to be inadequate for these systems, e.g., by severely underestimating the orbital magnetic moments with respect to experiment [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic anisotropy energy of magnetic nanocrystals (e.g., Fe, Co, Ni, etc.) is the subject of intense experimental [2][3][4][5] and theoretical [6][7][8][9][10][11] studies but the ability to grow well-defined magnetic crystalline nanostructures is also a major issue [12][13][14][15][16][17][18]. This is especially the case for Fe and Co nanoclusters that can adopt various crystalline bulk structures, in particular the body-centered-cubic (bcc) and the face-centered-cubic (fcc) structures in low dimensions [15,16].…”
Section: Introductionmentioning
confidence: 99%